Primary Sjogren's Syndrome presenting with Interstitial lung disease and Myositis - Kumkum Sarkar; Soumendra Nath Haldar; Shyamasish Das; Debananda Gonjhu; Netai Pramanik (Wolters Kluwer Medknow Publications, 2014)
Sjogren's syndrome (SS) is an autoimmune disease, is the most common autoimmune disease following rheumatoid arthritis but remains undiagnosed in more than half. The hallmark histopathological features of SS are periepithelial lymphocytic infiltration of the affected organs. Antibodies to SSA (Ro) and SSB (La) are characteristically associated with SS. The reported frequency of pulmonary involvement in primary SS varies widely, ranging from 9% to 75% and consists of various forms of small airway diseases and interstitial lung diseases (ILD). We are reporting a case of primary SS presenting with ILD and myositis.